2012
DOI: 10.1051/medsci/2012288015
|View full text |Cite
|
Sign up to set email alerts
|

Infections associées aux biofilms

Abstract: > Les biofilms sont des communautés de microorganismes en contact avec une surface. Bien que bénéfiques dans la plupart des environnements, les biofilms bactériens se développant sur des implants ou lors d'infections chroniques constituent des réservoirs de pathogènes à l'origine de nombreuses infections nosocomiales. Malgré la mise en oeuvre de mesures préventives, les biofilms sont difficiles à éradiquer en raison de leur tolé-rance caractéristique à des doses élevées d'antibiotiques. Cette revue présente le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 75 publications
0
8
0
1
Order By: Relevance
“…Bacteria continuously switch from a planktonic phenotype to a sessile one. This state variation is strategic for the cell as it allows a rapid adaptation to environmental conditions (Lebeaux and Ghigo, 2012).…”
Section: The Bacterial Biofilm a Community Way Of Lifementioning
confidence: 99%
“…Bacteria continuously switch from a planktonic phenotype to a sessile one. This state variation is strategic for the cell as it allows a rapid adaptation to environmental conditions (Lebeaux and Ghigo, 2012).…”
Section: The Bacterial Biofilm a Community Way Of Lifementioning
confidence: 99%
“…In human medicine, biofilms are known to contribute to a wide variety of infections and diseases including wound infections, implant related infections, lung infections, osteomyelitis, chronic otitis media, urinary tract infections, chronic sinusitis, dental plaque, endocarditis, etc. (23). Pseudomonas aeruginosa biofilm infection in cystic fibrosis patients is one of the most well-studied biofilm infections to date, and intense research has revealed both pathogenetic, diagnostic, and therapeutic breakthroughs, and has increased the life expectancy of these patients dramatically (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, biofilms contribute to a wide variety of tissue infections apart from wound infections. Urinary tract infections, osteomyelitis, device-related infection, chronic otitis media, chronic sinusitis, endocarditis, dental plaques, kidney stones, and lung infection (especially in cystic fibrosis patients) are just part of the repertoire of biofilms [45,46]. To date, very little is known about how biofilms are established in clinical infections, nor about when or how they become difficult to eradicate.…”
Section: Biofilm In Generalmentioning
confidence: 99%